Statistical Quality Control of Ultra High Temperature (UHT) Milk in PT XYZ - Ester Mastiur Sitorus; Ervina Mela (Indonesian Journal of Food Technology, 2022)
Ultra high temperature (UHT) milk is a product that is widely consumed because of its practicality and hygiene. PT XYZ is one of the industries that produces UHT milk with chocolate and strawberry flavors. Based on company records, there are variations in the protein content of the two products. The purpose of this study was to determine the average protein content of chocolate and strawberry milk on the control chart and to develop a cause-and-effect diagram to determine the factors that triggered variation in protein levels in PT XYZ's chocolate milk and strawberry milk. The research data was obtained from company records, which were then analyzed using MR control charts and fishbone diagrams. The results showed that there were values that were outside the control limits, both in the chocolate and strawberry flavor variants. The cause of the variability in the value of protein content in UHT milk in both chocolate and strawberry flavors comes from 4 factors. The machine factor is in the form of machine checking, which is still curative. The human factor is a lack of human resources and the absence of regular employee training. The factor of the method of using materials that are still manual Material factors are in the form of non-uniformity of sources and quality of raw materials for fresh milk from suppliers, and differences in quality and type of raw materials (between fresh milk and recombined milk).